A bibliometric analysis of polymer solutions injection in the oil recovery (Research, Society and Development, 2019)
Oil is still the main energy source in the world. The development of civilization brings with it an increase in energy demand, requiring from the research institutions new alternatives to enable an increase in production. Among these alternatives are the enhanced oil recovery (EOR) techniques. One such techniques is the injection of polymer solutions into oil reservoirs, which improves the mobility ratio between fluids and increases the recovery factor. This paper proposes a bibliometric revision on the injection of polymer solutions as EOR technique. Through the Web of Science platform, it analyzes the theme with four keyword refinements: “Enhanced oil recovery”, “polymer injection solution”, “recovery factor” and “experimental.” The articles resulting from the research were analyzed for the publication period defined between 2009 and 2018 to obtain current works. Subsequently, they were analyzed regarding the proposed theme. The results show a dominance of the publications of China followed by Iran. Collaboration networks between researchers have been analyzed to illustrate how groups relate to each other on the world. A data table with the main information about the papers was also developed. Three main lines of work were found: evaluation of properties and injection conditions in porous media, association of substances with polymer solutions for optimization of injection properties and injection results in real reservoirs.